Dinamika Kebijakan Pemerintah Kota Denpasar Terhadap Revitalisasi Pasar Sindu di Desa Sanur - hasibuan, Zulinda Romadhona; Erawan, I Ketut Putra; Noak, Piers Andreas (Jurnal Nawala Politika, 2019)
ABS TRACT   Tr aditional m arket c an not  be s eparated from human being,  i n order to full f i l l the f orm of b asic necessity s uch as Clothes, F oods, and Home b ecause these k i nd o f things c an not be formed and producing i t g oods a nd s ervice by i tself. T h us s ociety c an be easily to full fill t heir necessities by t he existence o f the market a s a place f or trading all g oods and products has be en s howed i n S i n du market development by economical point of vi ew followed by tourism s ector which i s c arrying S anur V i ll a ge i nto a r evolution. T he government has c o mmitted to r evitalize traditional market i n Denpasar City and one of the proof of the c o mmitment s hown by s upporting a nd a uthenticatring a program of Si n dhu Tr aditonal m arket’s r evitalization as i t agenda. T heory t hat used i n t his r e s earch are Rational Choice theory and A g enda S etting which utilized by the Q ualitative methods by g etting a n i nformation by deep i n terview. T he r esult o f this r esearch i s s howing a d i n amics of the government i n the process of r evitalization by authenticating that agenda and as   s upporting i dea which i s harmonized for both of s ector i n t his r evitalization agenda.   Keywords : Sindhu market, Government Support, Traditional Market’s Revitalization.